Assessment of Severe Apnoea through Voice Analysis, Automatic Speech, and Speaker Recognition Techniques. (14th June 2009) - Fernández Pozo Fernández Pozo, Rubén Rubén; Blanco Murillo Blanco Murillo, Jose Luis Jose Luis; Hernández Gómez Hernández Gómez, Luis Luis; López Gonzalo López Gonzalo, Eduardo Eduardo; Alcázar Ramírez Alcázar Ramírez, José José; Toledano Toledano, Doroteo T. Doroteo T.
Abstract : This study is part of an ongoing collaborative effort between the medical and the signal processing communities to promote research on applying standard Automatic Speech Recognition (ASR) techniques for the automatic diagnosis of patients with severe obstructive sleep apnoea (OSA). Early detection of severe apnoea cases is important so that patients can receive early treatment. Effective ASR-based detection could dramatically cut medical testing time. Working with a carefully designed speech database of healthy and apnoea subjects, we describe an acoustic search for distinctive apnoea voice characteristics. We also study abnormal nasalization in OSA patients by modelling vowels in nasal and nonnasal phonetic contexts using Gaussian Mixture Model (GMM) pattern recognition on speech spectra. Finally, we present experimental findings regarding the discriminative power of GMMs applied to severe apnoea detection. We have achieved an 81% correct classification rate, which is very promising and underpins the interest in this line of inquiry.